Selection bias at the heterosexual HIV-1 transmission bottleneck - Carlson, J; Schaefer, M; Monaco, D; Batorsky, R; Claiborne, D; Prince, J; Deymier, M; Ende, Z; Klatt, N; DeZiel, C; Lin, T; Peng, J; et al. (American Association for the Advancement of Science, 2014)
Heterosexual transmission of HIV-1 typically results in one genetic variant establishing systemic infection.We compared, for 137 linked transmission pairs, the amino acid sequences encoded by non-envelope genes of viruses in both partners and demonstrate a selection bias for transmission of residues that are predicted to confer increased in vivo fitness on viruses in the newly infected, immunologically naïve recipient. Although tempered by transmission risk factors, such as donor viral load, genital inflammation, and recipient gender, this selection bias provides an overall transmission advantage for viral quasispecies that are dominated by viruses with high in vivo fitness. Thus, preventative or therapeutic approaches that even marginally reduce viral fitness may lower the overall transmission rates and offer long-term benefits even upon successful transmission.